Factors Affecting Product Purchase Decisions at Griya Dien - Nazila, Qahira; Hermeindito (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This research examines and analyzes the factors affecting product purchase decisions at Griya Dien. The variables of this study consist of the dependent variable, namely purchasing decisions, and the independent variables, namely personal factors, psychological factors, cultural factors, and social factors. The sampling method used in this study is non-probability sampling with a total of 70 consumers of Griya Dien respondents. All hypotheses of this study were tested using multiple linear regression using SPSS 27. The results of this study indicate that personal factors have a positive and significant influence on purchasing decisions, psychological factors do not have a significant influence on purchasing decisions, cultural factors have a positive and significant influence on purchasing decisions, and social factors have a positive and significant influence on purchasing decisions